Conhecimento dos cirurgiões-dentistas e dos profissionais de emergências médicas sobre avulsão dentária no município de Fortaleza, Ceará - Araujo, Rebecca Bastos Rocha (2008)
The purpose of this study was to evaluate the knowledge of dentists, and health professional who work in emergency rooms (physicians, nurses and emergency medical technicians) regarding primary treatment for dental avulsion in Fortaleza, Ceará. The survey was based on a questionnaire. Data were collected in dental offices, public units, institutions which offer pos graduate courses, dental meetings and units of public medical emergency. The storage of the tooth in a liquid medium was recommended in 72,41%, but milk was indicated in 45,2% of these cases. In the presence of tooth vitality of the periodontal ligament, 34,67% answered correct, when vitality was not present 45,24% would not reimplante teeth. 18,7% of the health professionals from emergency rooms demontrated knowledge about tooth avulsion, while 38,7% had seen a patients who suffered tooth avulsion. Of these only 4% would reimplant the avulsed tooth and 91% would refer the patient to a dentist. They recommended storage of the tooth in a gauze or cotton in 57,7%. This study concluded that dentists and professionals from emergency rooms do not have adequate knowledge for treatment of these dental traumas. This fact generates on unfavorable prognosis of teeth that suffer avulsion. Thus educational campaigns are need to inform better these professional to give the best prognosis for traumatically avulsed tooth